2021
DOI: 10.1097/mbp.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dipping and nondipping pattern of blood pressure on subclinical left ventricular dysfunction assessed by two-dimensional speckle tracking in hypertensive patients

Abstract: The aim of this study was to evaluate the left ventricular (LV) function by conventional two-dimensional speckle tracking echocardiography (2D STE) to detect subclinical LV systolic dysfunction in patients with dipper and nondipper hypertension.Methods One hundred consecutive patients with hypertension were included in our study. Clinical evaluation, baseline laboratory investigations, 24 ambulatory blood pressure monitoring 2D echocardiographic examination and 2D STE were performed for all patients. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The majority of studies investigating LV remodelling in patients with different circadian BP patterns reported a significant deterioration in LV structure and diastolic function in non-dippers in comparison with dippers (21,22,26,28,29). This may be related to the association between nocturnal hypertension in non-dippers and LV remodelling induced by overactivated sympathetic nervous system, renin-angiotensin-aldosterone system, sleep apnoea syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies investigating LV remodelling in patients with different circadian BP patterns reported a significant deterioration in LV structure and diastolic function in non-dippers in comparison with dippers (21,22,26,28,29). This may be related to the association between nocturnal hypertension in non-dippers and LV remodelling induced by overactivated sympathetic nervous system, renin-angiotensin-aldosterone system, sleep apnoea syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical LV changes recently implemented in clinical studies may reveal subclinical and subtle impairments in LV function previously undetectable with conventional echocardiographic assessment. Although differences were noticed for longitudinal, circumferential and radial strains (25,26,28), major attention has been paid to GLS, which represents not only a robust echocardiographic parameter that reveals subtle impairment of LV function, but also a paramount predictor of adverse outcomes, including mortality. GLS turned out to be a more sensitive and reproducible parameter than conventional LVEF in general (34) and hypertensive population (19).…”
Section: Discussionmentioning
confidence: 99%